The Development of Social Responsibility Characteristics Using Electronic Story Books with Students in Grade 2 at Srinakharinwirot University Prasarnmit Demonstration School (Elementary) - Kreehirun, Chalermchon; Srikolchan, Anchalee (Arts of Management Journal, 2024)
The purposes of this research are as follows: 1) to develop an electronic storybook to promote social responsibility characteristics 2) to evaluate the effectiveness and outcomes of the electronic storybook and 3) to promote social responsibility characteristics of students. The research sample consists of students from Grade 2, Satit Prasarnmit Primary School, totaling 60 students from 2 selected classes out of 8, with 30 students per class. Data collection tools included electronic storybooks, "The Floating Lantern with the Big Brother Kla and the little sister Keaw," a suitability assessment questionnaire for electronic storybooks, an academic performance test, and social responsibility characteristics measurement. Statistical analysis used included mean, standard deviation, and intergroup non-independent t-test statistics. The research results found the following: 1. The quality of the developed electronic storybook is very good (x̄ = 4.53, S.D. = 0.39). 2. The electronic storybook has an effectiveness of 80.56/88.89, which is higher than the effectiveness criterion of 80/80, and has an impact index of 0.43. 3. The characteristics of social responsibility of targeted students in all three aspects, overall at a frequent practice level (x̄ = 4.45, S.D.= 0.64). This is demonstrated as follows: Aspect 1: Most students have a high frequency of self-responsibility (x̄ = 4.16, S.D.= 0.80). Aspect 2: Most students exhibit regular responsibility towards others (x̄ = 4.53, S.D.= 0.63). And in Aspect 3: Most students consistently demonstrate responsibility towards society and the environment (x̄ = 4.65, S.D.= 0.48). Furthermore, the average learning outcome scores of students’ post-learning academic performance test scores are significantly increased to 0.01 level of significance.